The effects of various respiratory physiotherapies after lung resection: a systematic review. (1st November 2020) - Larsen, Karoline Stentoft; Skoffer, Birgit; Gregersen Oestergaard, Lisa; Van Tulder, Maurits; Petersen, Annemette Krintel
ABSTRACT: Purpose : The purpose of this review was to investigate the effect of respiratory physiotherapy after lung resection on mortality, postoperative pulmonary complications (PPC), length of stay, lung volumes, and adverse events. Material and methods : Randomized or quasi-randomized controlled trials were searched in CENTRAL, PubMed, EMBASE, Cinahl, PEDro, and hand searching of related studies. Various respiratory physiotherapy interventions were compared to standard care, sham treatment, or no treatment. Two reviewers assessed eligibility and quality of studies using Cochrane guidelines. Meta-analyses were undertaken on subgroups of intervention. Results : Various types of positive pressure breathing, deep breathing exercises, and strength and aerobic exercises as a supplement to standard care did not show any significant effect over standard care in preventing mortality or PPC, reducing length of stay, or improving lung volumes. Conclusion : Prophylactic continuous positive airway pressure does not seem to affect rate of mortality and PPC, when compared with standard care embodying respiratory physiotherapy such as airway clearance techniques and assistance with early ambulation. However, further research is still needed to make a final conclusion. The effect of standard respiratory physiotherapy as a package is still unknown, and may or may not be effective in preventing PPC among patients undergoing lung resection.